Chapter La signoria dei d'Arco nell'alto Garda - Varanini, Gian Maria (Reti Medievali E-Book, 2023)
In the 14th and 15th centuries the Counts of Arco, settled immediately north of Lake Garda, played an important 'hinge function', linking politically now with the powers of the strong Italian cities. The Counts of Arco had close cultural and political relations especially with Brescia and Verona.